2005
DOI: 10.1002/mrc.1623
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage approach to automatic determination of1H NMR coupling constants

Abstract: (1)H NMR scalar coupling constants are a rich source of information on molecular structure, but their extraction from spectra can be less than straightforward. Previous approaches to J extraction include methods proposed by Hoye, Golotvin, and the 'modified J-doubling' method. Here we describe the ACCA method, currently implemented in the NMR package MestReC, which allows a high degree of automation in the extraction of coupling patterns even in the case of complex multiplets with sublinewidth splitting. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…. [40] We have measured the same previously unreported proton couplings of strychnine with our new pulse sequence obtaining similar but slightly higher values (see Supporting Information) together with an additional coupling constant, 5 J(H-15b,H-22), close to our experimental resolution of 1.0 Hz (calcd 0.7 Hz).…”
Section: Resultssupporting
confidence: 59%
“…. [40] We have measured the same previously unreported proton couplings of strychnine with our new pulse sequence obtaining similar but slightly higher values (see Supporting Information) together with an additional coupling constant, 5 J(H-15b,H-22), close to our experimental resolution of 1.0 Hz (calcd 0.7 Hz).…”
Section: Resultssupporting
confidence: 59%
“…Alternatively, two different options were proposed to certify the accuracy in such measurements: (i) the use of individualized scaling factors (AP + k*IP) and (ii) a data validation process from the individual analysis of the acquired IP and AP data and further comparison with the IPAP results. To demonstrate the accuracy of our measurements, Table compares the values extracted from the IPAP, J‐resolved and E.COSY patterns in Figs with those measured from the selHSQMBC‐IPAP and selHSQMBC‐TOCSY‐IPAP experiments previously published by our group, and also with other experimental data . It is shown that the IPAP technique provides values of the same order as those published by all these other methods.…”
Section: Resultsmentioning
confidence: 64%
“…In the case of NMR data, these speci c actions are the addition and/or removal of peaks, integration of signals, coupling constant and multiplicity calculation and assignment. Multiplicities are automatically inferred by known libraries [27,28] and are checked by additional rules to ensure the correctness of the results. The generated information such as the identi ed signals, coupling constants and multiplicity can be summarized in form of a signal list.…”
Section: Spectra Editor and Control Panel For One Dimensional 1 H Nmrmentioning
confidence: 99%